Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd005049.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmics for maintaining sinus rhythm after cardioversion of atrial fibrillation

Abstract: BackgroundAtrial fibrillation is the most frequent sustained arrhythmia. Atrial fibrillation frequently recurs after restoration of normal sinus rhythm. Antiarrhythmic drugs have been widely used to prevent recurrence, but the effect of these drugs on all-cause mortality and other clinical outcomes is unclear. This is an update of a review previously published in 2007, 2012 and 2015. risk of mortality was higher in people taking quinidine, although the confidence interval also includes the possibility of no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 133 publications
1
25
0
4
Order By: Relevance
“…The following antiarrhythmic drugs are recommended in patients with AF to maintain sinus rhythm, depending on underlying heart disease and comorbidities (Level of Evidence: A) : Amiodarone (314, 347-349)Dofetilide (332, 336)Dronedarone (350-352)Flecainide (347, 353)Propafenone (347, 354-357)Sotalol (347, 355, 358)…”
Section: Rhythm Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The following antiarrhythmic drugs are recommended in patients with AF to maintain sinus rhythm, depending on underlying heart disease and comorbidities (Level of Evidence: A) : Amiodarone (314, 347-349)Dofetilide (332, 336)Dronedarone (350-352)Flecainide (347, 353)Propafenone (347, 354-357)Sotalol (347, 355, 358)…”
Section: Rhythm Controlmentioning
confidence: 99%
“…Several systematic reviews have summarized the efficacy and safety of antiarrhythmic drugs for treating AF (347, 359, 363, 364). In a meta-analysis of 44 trials, antiarrhythmic drug therapy significantly reduced recurrence of AF (with a number needed to treat ranging from 2 to 9).…”
Section: Rhythm Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Sotalol is effective for reducing the incidence of recurrent AF in patients with paroxysmal AF [86] and after conversion to sinus rhythm [87]. Sotalol has not been shown to be effective for conversion of AF to sinus rhythm.…”
Section: Recommendations and Reasoningmentioning
confidence: 99%
“…(January et al, 2014) One of the potential reasons that rhythm control has not demonstrated superiority to rate control strategies is the ineffective and often unsafe nature of currently available anti-arrhythmic medications, which at best maintain sinus rhythm for 1 year in 50% of patients, and are associated with an increase in mortality. (Lafuente-Lafuente et al, 2007) When interrogating only patients who have achieved and maintained sinus rhythm, post-hoc analyses of rhythm vs. rate control strategies have shown a consistent pattern of improvement in quality of life measures. (Guédon-Moreau et al, 2010; Singh et al, 2006) In the PIAF and HOT CAFE trials for example, 6-minute walk times and maximal treadmill workloads were increased.…”
Section: Ablation Of Atrial Fibrillationmentioning
confidence: 99%